PREVALENCE OF Listeria monocytogenes IN FROZEN FISH IN BASRAH CITY MARKETS - Ghazi M. Jabir Al- Maliki (Basrah Journal of Veterinary Research)
ABSTRACT The present study was performed on 80 samples of frozen fish . The samples were collected from different shops in Basrah city . Listeria spp. Was isolated (13%) of frozen fish , also they were counted in the examined samples. The mean counts were 8.75 x 102 CFU/g. of the fish . L. monocytogenes differentially identified from other Listeria species and could he isolated at (5%) in frozen fish . The drug susceptibility characterization of L. monocytogenes cleared that all isolates (100%) were resistant to Ampicilline and Gentanicine . while the other used antibiotics showed different degrees of antimicrobial sensitivity reactions for streptomycin , Tetracycline , Rifampicine and cefotexim